2015
DOI: 10.5901/mjss.2015.v6n4s2p689
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sexual Harassment in Workplace: Experience of Employees in Hospitality Industry in Terengganu, Malaysia

Abstract: The issue of sexual harassment has certainly become more prominent in the last decade. As the increasing number of cases reported, many countries have taken statutory action to recognize it as an insultive conduct and at the same time to punish and prevent it. In the hotel industry particularly, sexual harassment has frequently reported as a key problem. Working in the hospitality industry often involves an employee with a number of different people in the course of delivering service. Thus, this study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Interestingly, the three conceptualized dimensions, namely (I) perceived societal barriers for career development, (II) perceived organizational barriers, and (III) sexual harassment, are conceivable as examples of the job demands concepts encompassed by the widely accredited theoretical models from the field of occupational health psychology [21] which have been previously referred to in the introductory paragraph of the current paper. Furthermore, the three dimensions highlight the challenges that working women in Iran have to face, which are consistent with those reported in the available literature [8][9][10][11][12][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, the three conceptualized dimensions, namely (I) perceived societal barriers for career development, (II) perceived organizational barriers, and (III) sexual harassment, are conceivable as examples of the job demands concepts encompassed by the widely accredited theoretical models from the field of occupational health psychology [21] which have been previously referred to in the introductory paragraph of the current paper. Furthermore, the three dimensions highlight the challenges that working women in Iran have to face, which are consistent with those reported in the available literature [8][9][10][11][12][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 86%
“…Concerning your own parents and siblings please rate the importance they have had for you") also requires answers on a 4-point scale, but the latter entails categorical answers, such as 1 = "all members (father, mother, siblings)", 2 = "only my mother", 3 = "only my father" and 4 = "only my siblings". Twelve items (6,7,8,10,12,13,19,20,21,22,26,28) require answers on a 3-point scale ranging from 1 = "definitely" to 3 = "not at all". Two items (2,9) require answers on a 5-point scale ranging from 1 = "fewer than I would wish" to 5 = "much more frequent".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…al., 2016). It also leads to a low-quality work environment (Einarsen et at., 2008) and exposes the employees towards offensive behavior and sexual coercion (Ali et al, 2015). The findings of this research also concur Thirlwall and colleagues' finding that, harassed employees produce lower job performance (Thirlwall et al, 2009).…”
Section: Analysis and Discussionsupporting
confidence: 83%
“…Alexander et al (2012) noted that bullying in hotel kitchens was a part of the culture there and that bullying had a significant negative influence on employee satisfaction and commitment. Ali et al (2015) claimed that employees in the hospitality industry who worked providing services for a variety of customers were exposed to various types of harassment. Furthermore, Yap and Ineson (2015) conducted a survey with interns and reported that the interns faced various types of workplace bullying resulting in negative feelings and deleterious influences on their physical health.…”
Section: Literature Review and Conceptual Model Workplace Bullying In The Hospitality Industrymentioning
confidence: 99%